2009
DOI: 10.1016/j.bmcl.2009.02.096
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and β-amyloid binding properties of rhenium 2-phenylbenzothiazoles

Abstract: As a first step toward the development of 99m Tc PiB analogs, we have synthesized six neutral Re 2-phenylbenzothiazoles via pendant or integrated approach. These Re compounds bind to Aβ 1-40 fibrils with fairly good affinities (K i = 10.0-88.6 nM) and have moderate lipophilicities (logP C18 = 1.21-3.26). The Re compounds prepared via the integrated approach are smaller in size, and therefore their corresponding 99m Tc analogs would have a greater chance of crossing the blood-brain barrier well. For potential c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 22 publications
5
21
0
Order By: Relevance
“…The aliphatic amino N-H group that has relatively higher pKa value was not deprotonated after Re complexation reaction, and therefore, the overall charge was balanced. These results were consistent with our previously reported results for the synthesis of 12 and 21 17 .…”
supporting
confidence: 94%
See 2 more Smart Citations
“…The aliphatic amino N-H group that has relatively higher pKa value was not deprotonated after Re complexation reaction, and therefore, the overall charge was balanced. These results were consistent with our previously reported results for the synthesis of 12 and 21 17 .…”
supporting
confidence: 94%
“…In order to obtain neutral Tc/Re complexes, we also added one small methyl group to one of the aliphatic amino groups. After such modification (see Scheme 1A), all three protons were lost after complexation with [Re(V)O] 3+ , and the overall charge of 2-ABT 1–5 was balanced, which is in agreement with our previously reported results from the synthesis of 6 17 .…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Because of the fast brain and plasma clearance observed in AD and in healthy subjects, the in vivo metabolism and instability of 123 I-IMPY may not provide an optimal signal-to-noise ratio. Additional candidates are being explored for SPECT of Aβ plaques in the brain (22,23). …”
mentioning
confidence: 99%
“…Elnagdi et al have reported several novel syntheses of azoles, azines, and azoloazines utilizing enaminonitriles as starting components [7][8][9]. On the other hand, the considerable biological and medicinal activities of benzothiazoles initiated considerable recent interest in the development of syntheses of these molecules [10][11][12][13][14][15][16][17][18]. In continuation of our interest in the synthesis of heterocycles containing a benzothiazole moiety [19,20], to identify new candidates that may be value in designing new, potent, selective and less toxic antimicrobial agents, we reported here a facial synthesis of some new pyrazole, isoxazole and pyrimidine derivatives pendant to a benzothiazole via the reactions of enaminonitrile with some nitrogen nucleophiles.…”
Section: Introductionmentioning
confidence: 99%